Coffee and pancreatic cancer risk among never‐smokers in the UK prospective Million Women Study. Issue 6 (28th December 2018) - Zhou, Charlie D; Kuan, Ai Seon; Reeves, Gillian K; Green, Jane; Floud, Sarah; Beral, Valerie; Yang, TienYu Owen
Abstract : Reported associations between coffee consumption and an increased risk of pancreatic cancer could be due to residual confounding by smoking and/or biased recall of coffee consumption in retrospective studies. Studying associations prospectively in never smokers should minimize these problems, but thus far such studies have included relatively small numbers of cases. In our study, 309, 797 never‐smoking women self‐reported typical daily coffee consumption at a mean age of 59.5 years (SD 5.0 years) and were followed up for a median of 13.7 years (IQR: 12.2–14.9) through record linkage to national health cancer and death registries. During this period, 962 incident cases of pancreatic cancers were registered. Cox regression was used to calculate adjusted relative risks [RRs] of incident pancreatic cancer with 95% confidence intervals [CIs] in relation to coffee consumption at baseline. After adjustment for potential confounding factors, including body mass index and alcohol consumption, RRs of pancreatic cancer in never‐smokers who reported usually consuming 1–2, 3–4, and ≥ 5 cups of coffee daily, compared to nondrinkers of coffee, were 1.02 (CI 0.83–1.26), 0.96 (0.76–1.22), and 0.87 (0.64–1.18), respectively (trend p = 0.2). A meta‐analysis of results from this cohort and 3 smaller prospective studies found little or no statistically significant association between coffee consumption and pancreatic cancer risk in never smokers (summary RR = 1.00, CI 0.86–1.17 for ≥2 vs . zero cups of coffee per day). Abstract : What's new? Reported associations between coffee consumption and pancreatic cancer risk could be due to residual confounding by smoking or recall bias of coffee consumption in retrospective studies. In this large prospective study and meta‐analysis restricted to never‐smokers, we found no significant association between coffee consumption and pancreatic cancer risk.